Antibiotic overuse after discharge from medical short-stay units. (24th November 2022) - Soper, Nathaniel S.; Appukutty, Abhinav J.; Paje, David; Petty, Lindsay A.; Flanders, Scott A.; Zhang, Qisu; Horowitz, Jennifer K.; Vaughn, Valerie M.
Abstract: Of 100 patients discharged from short-stay units (SSUs) with antibiotics, 47 had a skin and soft-tissue infection, 22 had pneumonia, and 21 had a urinary tract infection. Among all discharge antibiotic prescriptions, 78% involved antibiotic overuse, most commonly excess duration (54 of 100) and guideline discordant selection (44 of 100).